Pendampingan Masyarakat dalam Wisata Pelestarian Ekosistem Mangrove di Pulau Tidung Kepulauan Seribu Daerah Khusus Jakarta - Enjelita, Dian Tantri; Wulandari, Siti; Erfinda, Yosi (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2025)
The development of sustainable marine tourism on Tidung Island, Kepulauan Seribu, aims to promote environmental conservation and community participation in mangrove ecosystem management. The community development program focuses on increasing community awareness and participation in environmental conservation efforts. Mangroves are an important ecological system, found in tropical and subtropical regions, which function as carbon sinks and carbon sequestration. This community service aims to optimize the role of the community in environmental preservation and conservation. This activity was carried out for 3 (three) weeks starting from April 8 - 30, 2025 offline at the Tidung Island Tourism Village. The methods used were consultation with the community through FGD (Forum Group Discussion), observation, and social analysis. The program significantly contributed to the community's understanding of mangroves as an important ecological and water resource. However, there are still challenges related to community health and competition with other activities, so the focus should be on increasing community participation and resources to support mangrove conservation on Pulau Tidung Kecil. The community development program demonstrates that good cooperation between the community, government and environmental organizations is essential for the successful management of mangrove ecosystems on Pulau Tidung Kecil.